The epidemiological characteristics of patients with acute viral bronchiolitis admitted to the Pediatric Intensive Care Unit of the Hospital Universitário do Oeste do Paraná in 2023 (Research, Society and Development, 2025)
Acute viral bronchiolitis (AVB) is a viral lower respiratory tract infection that primarily affects children under one year of age and is more prevalent in males during specific seasonal periods in Brazil. The Western Paraná University Hospital is a leading healthcare center in the region and experiences a high demand for hospitalizations due to respiratory diseases in its Pediatric Intensive Care Unit, particularly AVB. The objective of this study was to analyze the epidemiological characteristics of patients with Acute Viral Bronchiolitis admitted to the Pediatric Intensive Care Unit of the Western Paraná University Hospital in 2023. This observational, cross-sectional study analyzed the medical records of children admitted in 2023. During this period, 23 patients were admitted with a confirmed diagnosis of AVB. Contrary to reports in the literature, females predominated. Most cases occurred in May and June, with a higher incidence of respiratory syncytial virus infection. All patients were under 12 months of age and developed complications, primarily bronchopneumonia and Severe Acute Respiratory Syndrome. More than 50% required invasive mechanical ventilation, and 91.3% received oxygen therapy; all received respiratory physiotherapy as part of their clinical management. These findings suggest possible changes in the epidemiological profile of AVB, while confirming aspects previously described in the literature. Therefore, further studies are needed to further analyze clinical progression, therapeutic strategies, and the impact of comorbidities on disease severity.